Fiscal Redistribution And Income Inequality In Latin America - Goñi, Edwin (The World Bank, 2008)
Income inequality in Latin America ranks among the highest in the world. It can be traced back to the unequal distribution of assets (especially land and education) in the region. But the extent to which asset inequality translates into income inequality depends on the redistributive capacity of the state. This paper documents the performance of Latin American fiscal systems from the perspective of income redistribution using newly-available information on the incidence of taxes and transfers across the region. The findings indicate that: (i) the differences in income inequality before taxes and transfers between Latin America and Western Europe are much more modest than those after taxes and transfers; (ii) the key reason is that, in contrast with industrial countries, in most Latin American countries the fiscal system is of little help in reducing income inequality; and (iii) in countries where fiscal redistribution is significant, it is achieved mostly through transfers rather than taxes. These facts stress the need for fiscal reforms across the region to further the goal of social equity. However, different countries need to place different relative emphasis on raising tax collection, restructuring the tax system, and improving the targeting of expenditures